Endodontic management of a maxillary lateral incisor with an unusual root dilaceration diagnosed with cone beam computed tomography - Mahmoud Mohammed Eid Mahgoub; Ahmed Abdel Rahman Hashem; Hany Mohamed Aly Ahmed (Wolters Kluwer Medknow Publications, 2017)
Anterior teeth may have aberrant anatomical variations in the roots and root canals. Root dilaceration is an anomaly characterized by the displacement of the root of a tooth from its normal alignment with the crown which may be a consequence of injury during tooth development. This report aims to present a successful root canal treatment of a maxillary lateral incisor with unusual palatal root dilaceration (diagnosed with cone beam computed tomography) in which the access cavity was prepared from the labial aspect of the tooth to provide a straight line access to the root canal system which was instrumented using OneShape rotary file system and precurved K-files up to size 50 under copious irrigation of 2.5% NaOCl using a side-vented irrigation tip. The canal was then obturated using the warm vertical compaction technique.